2014
DOI: 10.3389/fimmu.2014.00128
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of DNA Methylation, Copy Number Variation, and Gene Expression in Monozygotic Twins Discordant for Primary Biliary Cirrhosis

Abstract: Primary biliary cirrhosis (PBC) is an uncommon autoimmune disease with a homogeneous clinical phenotype that reflects incomplete disease concordance in monozygotic (MZ) twins. We have taken advantage of a unique collection consisting of genomic DNA and mRNA from peripheral blood cells of female MZ twins (n = 3 sets) and sisters of similar age (n = 8 pairs) discordant for disease. We performed a genome-wide study to investigate differences in (i) DNA methylation (using a custom tiled four-plex array containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 46 publications
2
45
0
1
Order By: Relevance
“…How these factors are molecularly involved in PBC onset remains unclear. Elsewhere, it was reported that X-chromosome gene expression instability might also participate in female predominance in the disease [64,65], and that monozygotic twins and sisters discordant for PBC exhibited particular epigenetic differences [66]. These collectively support the notion that epigenetic factors influence the onset of PBC.…”
Section: Epigenetics On Pbcmentioning
confidence: 67%
“…How these factors are molecularly involved in PBC onset remains unclear. Elsewhere, it was reported that X-chromosome gene expression instability might also participate in female predominance in the disease [64,65], and that monozygotic twins and sisters discordant for PBC exhibited particular epigenetic differences [66]. These collectively support the notion that epigenetic factors influence the onset of PBC.…”
Section: Epigenetics On Pbcmentioning
confidence: 67%
“…More recently performed genome-wide study supports consistent differences in discordant twins and siblings for methylation profiles of 60 gene regions [60]. Among 60 differentially methylated regions, 51 genes located to the X chromosome and 9 genes located to autosomal chromosomes.…”
Section: Dna Methylationmentioning
confidence: 67%
“…In the affected twin in discordant MZ pairs, the gene expression profile, copy number variants resulting from duplications and rearrangement, and DNA methylation, an important epigenetic modification, all differ markedly from the unaffected twin control [60]. These data from MZ twin studies, despite lacking mechanisms, are sufficient to suggest that PBC not only is influenced by genetic factors, but also by epigenetic influences.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations